El liderazgo estratégico como factor de desarrollo organizacional en la Compañía de taxi ejecutivo Guanujo expres TAXGUANUJO S.A. de la parroquia Guanujo cantón Guaranda provincia Bolívar año 2019 - Chalco Sandoval, Alexandra Patricia (2019)
This research work was carried out with the purpose of determining the way in which strategic leadership is being carried out to improve the development of the company, in the same way flaws are determined that impede its progress. In the investigation, objectives were established that allowed to determine, the factors that affect the development of the company, a theoretical-scientific analysis of the variables was carried out, and therefore the design of an Organizational Development model through action research. Field research was applied, which allowed information to be collected in the place of the events, that is, the survey was applied to the shareholders and the interview to the Manager, in which failures were determined in the managerial functions, that is, they are not defined correctly, the absence of Organizational Development models, the low educational level in administrative staff, as well as there is a weak motivation and training, those shortcomings allow to establish solutions, in which the beneficiaries are all those who are part of the company. The methods that have been implemented in the investigative process were, the deductive, analytical and scientific inductive method, in the same way the research techniques and instruments in which the survey, interview and questionnaire have been worked, this allowed to gather necessary information and timely for research. Due to the existing shortcomings in the company, it is considered necessary to design an Organizational Development model, through Action Research, the same as part of the collection of necessary information and subsequently, through feedback, perform their respective action, that is, Achieving a change in the organization. Finally, conclusions and recommendations are made so that the company achieves improvements in its development and therefore increases profitability. The research carried out will serve as a reference for those researchers who have the need to carry out similar work, in order to solve problems detected in all types of organizations. Keywords: Strategic Leadership, Organizational Development, Action Research